Ibadah Sebagai Tujuan Penciptaan Manusia: Kajian Tafsir Ayat-Ayat Ibadah Dalam Al-Qur’an - Ahmad Junaidi; Syarif Hidayah Tulloh; Samiun Alim; Edy Hasan Hasibuan; Edi Hermanto (CV. ITTC INDONESIA, 2025)
Worship is a fundamental concept in Islamic teachings, directly related to the purpose of human creation. However, in the practice of Muslims, worship is often understood as a limited formal ritual activity, thus not fully grasping it as a concept encompassing all dimensions of life. Therefore, this article aims to examine the verses of the Quran and the hadith of the Prophet Muhammad (peace be upon him) relating to worship to confirm that worship is the primary purpose of human creation. This research uses a qualitative approach with library research, with the primary data sources being the Quran and the hadith of the Prophet Muhammad (peace be upon him), supported by relevant Islamic books and scholarly articles. The data were analyzed using thematic descriptive-analytical methods. The results show that worship, from the perspective of the Quran and hadith, is not limited to ritual worship but encompasses all human life activities carried out with sincere intentions and in accordance with the guidance of sharia. Worship is also related to human efforts to fulfill their role as servants of God and prepare for life in this world and the hereafter in accordance with the purpose of their creation.